Quality assurance in contemporary Islamic Universities: issues and challenges - Kazeem, Bakare; Hashim, Che Noraini (IIUM Press, 2014)
The inability of contemporary Islamic higher institutions of learning to produce human capital of the “right mind and sound thought” has cast doubt on the goals and objectives of Islamic Universities of the present milieu. Change is imperative. The purpose of this article is to critically analyze some issues and challenges of quality assurance confronting Islamic universities and propose a quality assurance model that stems from leadership concepts rooted in Quranic tenets. Admittedly, some of the written goals of contemporary Islamic universities with respect to quality assurance had been partially fulfilled. However, compared with other contemporary universities, quality assurance in Islamic universities has not lived up to expectations, especially in terms of creative innovations and inventions, that are beneficial for all humanity. These weaknesses could be attributed to lack of leadership quality to spearhead innovative projects, and subsequent brain drain due to the exodus of bright Muslim minds migrating to ‘greener pastures’. The paper offers strategies for improving quality assurance in Islamic universities, with special emphasis on good governance and leadership.